Analysis of Drug Planning and Procurement in the Pharmaceutical Installation of Muhammadiyah General Hospital North Sumatera - Tanjung, Sri Maryani; Harahap, Juliandi; Nasution, Ramadhani Syafitri (PROMOTOR, 2024)
Planning of pharmaceutical preparations, medical devices and BMHP (Medical Consumables) is the initial stage to determine the type and amount of pharmaceutical preparations, medical devices and BMHP that suit needs. Procurement is an activity to realize planned and approved needs, through the purchase, production/manufacture of pharmaceutical preparations, and donations/dropping grants. This type of research uses research Descriptive Qualitative With research methods aim to make a picture or description of a situation objectively. This research was conducted using a semi-structured interview method that was included in the category Indepth Interview Namely free interviews so that the implementation is wider when compared to structured interviews. This research was conducted at RSU Muhammadiyah North Sumatra in December 2023. Based on the results of research on drug planning and procurement at the Muhammadiyah Hospital in North Sumatra using the consumption method carried out based on sales patterns or depleted stocks in pharmaceutical warehouses. The distribution of drugs from pharmaceutical warehouses to pharmaceutical installations is often delayed so that pharmaceutical services to patients are disrupted and cause patients to wait a long time. The obstacles seen in drug procurement are still not optimal, this is because there are empty and slow-moving drugs. The conclusion in this study is the planning and procurement of drug availability at the Muhammadiyah Hospital North Sumatra in improving the pharmaceutical service system to be better, planning is carried out to avoid drug buildup and expiration. ABC method analysis should be applied so that the data is more accurate, not only using the consumption method.